Teknik Distraksi Virtual Reality Dapat Mempengaruhi Tingkat Kecemasan Pada Pasien Hemodialisis: Virtual Reality Distraction Technique Can Impact the Anxiety Level in Hemodialysis Patients - Nia Wahda Aprilia; Susaldi, Susaldi; Bambang Suryadi (MPI Press, 2022)
Introduction: Chronic Kidney Disease (CKD) is a disease in which the kidneys experience dysfunction due to structural damage (destruction), so the kidneys have difficulty in maintaining metabolism and electrolyte and fluid homeostasis, which is characterized by the accumulation of metabolic waste products in the body. In general, many patients with Chronic kidney disease have psychological disorders, especially patients undergoing hemodialysis, most of the psychological disorders found are anxiety. Anxiety is a form of worry and discomfort that is being experienced, due to a certain situation. Virtual Reality distraction technique is a non-pharmacological therapy that utilizes advances in technology, distraction is a therapy that is carried out by diverting the patient's attention, the use of Virtual Reality distraction provides a 3-dimensional effect so that it can make the patient seem to be in a virtual world. Objective: This study aims to determine the effect of virtual reality distraction techniques on the anxiety level of hemodialysis patients. Method: the method in this research is pre-experimental quantitative research with a group pretest-posttest design model. The population in this study were all hemodialysis patients at the Hemodialysis Clinic Avio Prima Ciledug as many as 30 people using a total sampling technique. Data was collected using a standard Zung Self Rating Anxiety Scale questionnaire which consisted of 20 question items that were posed to patients before and after treatment. The test results were analyzed using the Wilcoxon signed-rank test. Results: Based on the results of statistical tests obtained p-value 0.000 < 0.05. Conclusion: There is an effect of virtual reality distraction techniques on the anxiety level of hemodialysis patients.